Anti-microbial activity of chrysomycin a produced by streptomyces sp. against mycobacterium tuberculosis - Balaji, Muralikrishnan; Dan, Vipin Mohan; Joseph, Vinodh; Jamsheena, Vellekkatt; Ramachandran, Ranjit; Thomas, Sabu; Dastager, Syed Gulam; Kumar, K. Santhosh; Lankalapalli, Ravi Shankar; Kumar, R. Ajay (RSC Advances, 2017)
Limited efficacy of the BCG (Bacillus Calmette–Guérin) vaccine against adult tuberculosis and the emergence of resistance to existing anti-tuberculosis drugs compel discovery of novel antibiotics against Mycobacterium tuberculosis. Actinomycetes are still an attractive platform for the discovery of new antimicrobials, especially from untapped natural hotspots, despite the belief that they are an exhausted resource after repeated re-discoveries. Herein we report the isolation and identification of chrysomycin A from an actinomycete isolated from a coastal area in Kerala. We show for the first time that it has antimycobacterial activity. It was found to be bactericidal to planktonic and intracellular M. tuberculosis with an MIC of 3.125 μg mL⁻¹; it is non-hemolytic and has negligible cytotoxicity. The actinomycete that produces chrysomycin A was found to be a Streptomyces sp. through 16S rRNA gene sequencing.

Streptomyces sp metabolite(s) promotes Bax mediated intrinsic apoptosis and autophagy involving inhibition of mTOR pathway in cervical cancer cell lines - Dan, Vipin Mohan; Muralikrishnan, Balaji; Sanawar, Rahul; Vinodh, J. S.; Burkul, Bhushan Bapusaheb; Srinivas, Kalanghad Puthankalam; Lekshmi, Asha; Pradeep, N. S.; Dastager, Syed G.; Santhakumari, B.; Santhoshkumar, Thankayyan R.; Kumar, R. Ajay; et al. (Scientific Reports, 2018)
In cervical cancer, the association between HPV infection and dysregulation of phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway (PI3K/AKT/mTOR pathway) places mTOR as an attractive therapeutic target. The failure of current treatment modalities in advanced stages of this cancer and drawbacks of already available mTOR inhibitors demand for novel drug candidates. In the present study we identified the presence of a mTOR inhibitor in an active fraction of the ethyl acetate extract of Streptomyces sp OA293. The metabolites(s) in the active fraction completely inhibited mTORC1 and thereby suppressed activation of both of its downstream targets, 4E-BP1 and P70S6k, in cervical cancer cells. In addition, it also stalled Akt activation via inhibition of mTORC2. The mechanism of mTOR inhibition detailed in our study overcomes significant drawbacks of well known mTOR inhibitors such as rapamycin and rapalogs. The active fraction induced autophagy and Bax mediated apoptosis suggesting that mTOR inhibition resulted in programmed cell death of cancer cells. The molecular weight determination of the components in active fraction confirmed the absence of any previously known natural mTOR inhibitor. This is the first report of complete mTOR complex inhibition by a product derived from microbial source.

Molecular networking and whole-genome analysis aid discovery of an angucycline that inactivates mTORC1/C2 and induces programmed cell death - Dan, Vipin Mohan; Vinodh, J. S.; Sandesh, C. J.; Sanawar, Rahul; Lekshmi, Asha; Kumar, R. Ajay; Kumar, T. R. Santhosh; Marelli, Uday Kiran; Dastager, Syed G.; Pillai, M. Radhakrishna (ACS Chemical Biology, 2020)
Rediscovery of known compounds and time consumed in identification, especially high molecular weight compounds with complex structure, have let down interest in drug discovery. In this study, whole-genome analysis of microbe and Global Natural Products Social (GNPS) molecular networking helped in initial understanding of possible compounds produced by the microbe. Genome data revealed 10 biosythethic gene clusters that encode for secondary metabolites with anticancer potential. NMR analysis of the pure compound revealed the presence of a four-ringed benz[a]anthracene, thus confirming angucycline; molecular networking further confirmed production of this class of compounds. The type II polyketide synthase gene identified in the microbial genome was matched with the urdamycin duster by BLAST analysis. This information led to ease in identification of urdamycin E and a novel natural derivative, urdamycin V, purified from Streptomyces sp. OA293. Urdamycin E (Urd E) induced apoptosis and autophagy in cancer cell lines. Urd E exerted anticancer action through inactivation of the mTOR complex by preventing phosphorylation at Ser 2448 and Ser 2481 of mTORC1 and mTORC2, respectively. Significant reduction in phosphorylation of the major downstream regulators of both mTORC1 (p70s6k and 4e-bp1) and mTORC2 (Akt) were observed, thus further confirming complete inhibition of the mTOR pathway. Urd E presents itself as a novel mTOR inhibitor that employs a novel mechanism in mTOR pathway inhibition.

Untargeted metabolomics reveals alterations in metabolites of lipid metabolism and immune pathways in the serum of rats after long-term oral administration of Amalaki rasayana - Kumar, Vikas; Kumar, A. Aneesh; Joseph, Vinod; Dan, Vipin Mohan; Jaleel, Abdul; Kumar, T. R. Santhosh; Kartha, Chandrasekharan C. (Molecular and Cellular Biochemistry, 2020)
Amalaki rasayana, a traditional preparation, is widely used by Ayurvedic physicians for the treatment of inflammatory conditions, cardiovascular diseases, and cancer. Metabolic alterations induced by Amalaki rasayana intervention are unknown. We investigated the modulations in serum metabolomic profiles in Wistar rats following long-term oral administration of Amalaki rasayana. Global metabolic profiling was performed of the serum of rats administered with either Amalaki rasayana (AR) or ghee + honey (GH) for 18 months and control animals which were left untreated. Amalaki rasayana components were confirmed from AR extract using HR-LCMS analysis. Significant reductions in prostaglandin J2, 11-dehydrothromboxane B2, and higher levels of reduced glutathione and glycitein metabolites were observed in the serum of AR administered rats compared to the control groups. Eleven different metabolites classified as phospholipids, glycerophospholipids, glucoside derivatives, organic acids, and glycosphingolipid were exclusively observed in the AR administered rats. Pathway analysis suggests that altered metabolites in AR administered rats are those associated with different biochemical pathways of arachidonic acid metabolism, fatty acid metabolism, leukotriene metabolism, G-protein mediated events, phospholipid metabolism, and the immune system. Targeted metabolomics confirmed the presence of gallic acid, ellagic acid, and arachidonic acid components in the AR extract. The known activities of these components can be correlated with the altered metabolic profile following long-term AR administration. AR also activates IGF1R-Akt-Foxo3 signaling axis in heart tissues of rats administered with AR. Our study identifies AR components that induce alterations in lipid metabolism and immune pathways in animals which consume AR for an extended period.
Keywords: Amalaki rasayana; Ayurvedic medicines; Leukotriene metabolism; Lipid metabolism; Metabolic profiling

Artificial intelligence in microbial natural product drug discovery: current and emerging role - SahayaSheela, Vinodh J.; Lankadasari, Manendra B.; Dan, Vipin Mohan; Dastager, Syed G.; Pandian, Ganesh N.; Sugiyama, Hiroshi (Natural Product Reports, 2022)
Covering: up to the end of 2022 Microorganisms are exceptional sources of a wide array of unique natural products and play a significant role in drug discovery. During the golden era, several life-saving antibiotics and anticancer agents were isolated from microbes; moreover, they are still widely used. However, difficulties in the isolation methods and repeated discoveries of the same molecules have caused a setback in the past. Artificial intelligence (AI) has had a profound impact on various research fields, and its application allows the effective performance of data analyses and predictions. With the advances in omics, it is possible to obtain a wealth of information for the identification, isolation, and target prediction of secondary metabolites. In this review, we discuss drug discovery based on natural products from microorganisms with the help of AI and machine learning.